SOSIALISASI PEMILU BAGI PEMILIH PEMULA - asril, aprinal adila; Sari, Putri Gemala; Putra, Roni Tri; Adona, Fitri; Nita, Sri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
New voters play an important role in the election because as many as 35-40% of all voters are new voters. In this way, the number of first-time voters is very large, so that citizens' rights to exercise their right to vote should not be insignificant as a result of unexpected mistakes, for example, do not let them already have the right to vote and not be able to exercise their right to vote because they are not registered or there are still many errors in exercise their right to vote, etc.Dian Andalas Private High School is located in Komp. Unand Ulu Gadut. There are 70 students from Dian Andalas Private High School who are in the category of beginner voters in the 2024 elections. There are still many students who do not understand the importance of voting rights in general elections and do not know the procedures for granting voting rights at polling stations.The aim to be achieved from this service activity is to provide insight and improve skills for Dian Andalas Private High School students in their participation in the upcoming 2024 elections.The output target that will be achieved is the students of the Dian Andalas Private High School, by carrying out this activity, it is hoped that the students of the Dian Andalas Private High School, Padang, will participate in the general election and know the procedures for voting in the general election.